Evaluation of the relationship between strength, quality grade, microstructure and abrasion of concrete - Abhijit Warudkar; S Elavenil (Materials Research Express, 2021)
Surface abrasion is the most general cause of concrete deterioration. Abrasion can be a catalyst for structural failures, as abrasion leads to structural cracks and reinforcement corrosion. The abrasion of the concrete surface is a reflection of the compressive strength and quality grading of the concrete. This study aims to examine the relationship between abrasion, compressive strength, and quality grading of concrete. The mechanical properties, quality grading, and abrasion of the concrete were evaluated based on the compressive strength (IS 516), ultrasonic pulse velocity (IS 13311), and sandblasting abrasion testing (IS 9284), respectively. Abrasion resistance increased with compressive strength and ultrasonic pulse velocity. The study was supported by microstructural analysis and surface chemical composition of the concrete. It was concluded that quality grading, sound microstructure, and abrasion resistant concrete with higher compressive strength along with the use of superplasticiser leads to better abrasion resistance.